CBSE students can refer to NCERT Solutions for Class 7 Maths Chapter 1 Integers Ex 1.2 Textbook Questions and Answers are provided by experts in order to help students secure good marks in exams.

## Class 7 Maths NCERT Solutions Chapter 1 Integers Ex 1.2

**Ex 1.2 Class 7 Maths Question 1.**

Write down a pair of integers whose:

**(a)** The sum is – 7

**(b)** Difference is -10

**(c)** Sum is 0

**Solution.**

**(a)** A pair of integers whose sum is – 7 can be (- 1) and (- 6).

∵ (- 1) + (- 6) = – 7

**(b)** A pair of integers whose difference is -10 can be (- 11) and (- 1)

∵ – 11 – (- 1) = – 11 + 1 = – 10

**(c)** A pair of integers whose sum is 0 can be 1 and (- 1).

∵ (- 1) + (1) = 0.

**Ex 1.2 Class 7 Maths Question 2.**

**(a)** Write a pair of negative integers whose difference gives 8.

**(b)** Write a negative integer and a positive integer whose sum is – 5.

**(c)** Write a negative integer and a positive integer whose difference is – 3.

**Solution.**

**(a)** A pair of negative integers whose difference gives 8 can be – 12 and – 20.

∵ (-12) – (- 20) = -12 + 20 = 8 .

**(b)** A negative integer and a positive integer whose sum is -5 can be – 13 and 8.

∵ (- 13) + 8 = -13 + 8 = – 5

**(c)** A negative integer and a positive integer whose difference is -3 can be – 1 and 2.

∵ (- 1) – 2 = – 1 – 2 = – 3

**Ex 1.2 Class 7 Maths Question 3.**

In a quiz, team A scored – 40, 10, 0, and Team B scored 10, 0, – 40 in three successive rounds. Which team scored more? Can we say that we can add integers in any order?

**Solution.**

The total score of team A = (- 40) + 10 + 0 = (- 40) + 10 = – (40 – 10) = – 30

Total score of team B = 10 + 0 + (- 40) = 10 + (- 40) = – (40 – 10) = – 30

So, both the teams scored equally. Yes! We can say that we can add integers in any order.

**Ex 1.2 Class 7 Maths Question 4.**

Fill in the blanks to make the following statements true:

- (-5) + (-8) = (-8) + (………)
- -53 + ……. = -53
- 17 + …… = 0
- [13 + (-12)] + (……) = 13 + [(-12) + (-7)]
- (-4) + [15 + (-3)] = [-4 + 15] + ……

**Solution.**

- (-5) + (-8) = (-8) + (-5)
- -53 + 0 = -53
- 17 + (-17) = 0
- [13 + (-12)] + (-7) = (13) + [(-12) + (-7)]
- (-4) + [15 + (-3)] = [(-4 ) + 15] + (-3)